Հայ պատմագրության ուսումնասիրման քաղաքական դիտանկյան ներածական հարցեր - Սարգսյան, Աշոտ
Armenian literature of the 5th century has been deservedly characterized as "Golden Age" thanks to the multitude and high standards of translated and original works. The first original works are historiographic, they are not only numerous but also display high standards of historiographic thought. In Armenian studies, this phenomenon has mainly been explained on a cultural basis; the only precondition was the creation of the Armenian alphabet at the beginning of the 5th century. However, this explanation, being natural, cannot be considered comprehensive. There are still a number of questions that can be answered by the study of historiography from the political point of view, particularly in the context of the preliminary discussion of the following questions: A) the relationship between culture and politics, B) the connection between historiography and ideology in general; the influence of this connection on events, realia and objective reality from the aspects of both the present and the past, C) consideration of religion not only as a cultural but, above all, a political phenomenon; relationship between religion and power. At the same time, all three problems, due to their constancy, have a wide temporal scope and, as manifestations of the struggle for power, have come down to our days from ancient times. One should search for the explanation of the Armenian "Golden Age," "powerful cultural explosion" and "magic hand" in this political context. Армянская литература V века заслуженно характеризуется как "Золотой век", учитывая обилие и высокий уровень переведенных и самостоятельных памятников. Первые самостоятельные труды – историографические памятники, которые также отличаются не только большим числом, но и высоким уровнем историографической мысли. Этот феномен интерпретировался в арменоведении на культурной основе, а его единственной предпосылкой считалось создание армянской письменности в начале V века. Такое объяснение, будучи естественным, не может считаться полным. Остается еще ряд вопросов, на которые можно ответить, изучив историографию с политической точки зрения, в частности, в контексте предварительного обсуждения следующих вопросов: А) взаимосвязь между культурой и политикой. Б) связь историографии и идеологии в целом; влияние этой связи на события, реалии, объективную реальность, с точки зрения как настоящего, так и прошлого. В) рассмотрение религии не только как культурного, но, прежде всего, как политического феномена; взаимосвязь между религией и властью. При этом все три проблемы, в силу своей постоянности, имеют широкий временной охват и, как проявления борьбы за власть, дошли до наших дней с древних времен. В этой политической плоскости следует искать объяснение армянского "Золотого века", "мощного культурного взрыва" и "волшебной руки".
Keywords: Պատմագրություն